The Bright Elusive Butterfly of Value in Health Technology Development; Comment on “Providing Value to New Health Technology: The Early Contribution of Entrepreneurs, Investors, and Regulatory Agencies” - Trisha Greenhalgh; Nick Fahy; Sara Shaw (International Journal of Health Policy and Management, 2018)
The current system of health technology development is characterised by multiple misalignments. The “supply” side (innovation policy-makers, entrepreneurs, investors) and the “demand” side (health policy-makers, regulators, health technology assessment, purchasers) operate under different – and conflicting – logics. The system is less a “pathway” than an unstable ecosystem of multiple interacting sub-systems. “Value” means different things to each of the numerous actors involved. Supply-side dynamics are built on fictions; regulatory checks and balances are designed to assure quality, safety and efficacy, not to ensure that technologies entering the market are either desirable or cost-effective. Assessment of comparative and cost-effectiveness usually comes too late in the process to shape an innovation’s development.